Trend 2000 - 2010. Energy Information Administration. International Energy Statistics: Renewables Biofuel Consumption | Country: Greenland | Indicator: Total Biofuels Consumption (Thousand Barrels Per Day), 2000-2010. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 004-014-036. - Energy Information Administration (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Energy Information Administration (2015). International Energy Statistics: Renewables Biofuel Consumption | Country: Greenland | Indicator: Total Biofuels Consumption (Thousand Barrels Per Day), 2000-2010. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 004-014-036. Dataset: Provides statistics on consumption of biofuels by country, as available. Biofuels are liquid fuels and blending components produced from biomass feedstocks, used primarily for transportation. The dataset provides data for 220 countries, as available, on energy-related metrics, including total and crude oil production, oil consumption, natural gas production and consumption, coal production and consumption, electricity generation and consumption, primary energy, energy intensity, CO2 emissions and imports and exports for all fuels. Data are sourced from Energy Information Administration research, as well as from national and international agencies, listed at http://www.eia.gov/cfapps/ipdbproject/docs/sources.cfm. Category: Energy Resources and Industries, International Relations and Trade Source: Energy Information Administration The Energy Information Administration (EIA), created by Congress in 1977, is an independent statistical and analytical agency within the United States Department of Energy. Its mission is to provide policy-independent data, forecasts, and analyses to promote sound policy making, efficient markets, and public understanding regarding energy and its interaction with the economy and the environment. http://www.eia.doe.gov/ Subject: Energy Consumption, Renewable Energy, Biofuels